Destruction of bonds between soil particles in the process of water erosion - O. G. Bushueva; A. V. Gorobets; N. G. Dobrovol’Skaya; Z. P. Kiryukhina; S. F. Krasnov; G. A. Larionov; L. F. Litvin (Бюллетень Почвенного института им. В.В. Докучаева)
It is known that tensile strength of soil samples is by three orders of magnitude greater than the shear stresses on the bottom of slope streams responsible for the detachment and transport of soil particles by water current. C.E. Mirtskhulava believed that detachment of soil particles by water current occurs due to the fatigue destruction of bonds between soil particles.Taking this fact into account, tensile strength is lower by two orders of magnitude. M.A. Nearing had an opinion that detachment of soil particles occurs in the points of separation of vortices from the bottom of the stream, where the shear stress is by two orders of magnitude higher than the average. These approaches did not explain overcoming by slope streams of the cohesion forces between soil particles. Studies of the influence of water temperature on the washout rate of model samples have shown that the soil erosion is highly dependent on the water temperature, which is close to the Van’t Hoff’s rule. This means that destruction of bonds between soil particles is probably the result of interaction between the soil solid phase and water molecules. Experiments have also shown that destruction of bonds between soil particles in the sample of chernozem monoaggregate soil occurs under a layer of still water. Upon the start of the water flow, particles that lost bond with the rest of the soil body immediately break away. The number of particles with disrupted bonds grows with the duration of the sample exposure to still water, although with some flattening. Experiments confirm the validity of the hypothesis of non-hydraulic nature of forces that disrupt inter-aggregate bonds during water erosion.